Age‐ and sex‐associated morphological variations of metatarsal torsional patterns in humans. Issue 8 (6th July 2017) - Kitashiro, Masateru; Ogihara, Naomichi; Kokubo, Tetsuro; Matsumoto, Morio; Nakamura, Masaya; Nagura, Takeo
Abstract : It has been demonstrated that the torsional patterns of the metatarsal heads are associated with the presence or absence of the medial longitudinal arch in hominoid feet. The relatively untwisted second metatarsal is unique in humans, but that of the African apes is much more inverted, suggesting that the torsion of the second metatarsal might represent the overall shape and flatness of the foot. Some clinical studies have recently argued that the onset of foot pathologies such as hallux valgus might be related to the torsional pattern of the metatarsals. However, to date, no studies have systematically investigated the morphological variations of the torsional patterns of human metatarsals. In this study, therefore, the aim was to clarify the age‐ and sex‐associated variations in the torsional patterns of human metatarsals using three‐dimensional computed tomography. The torsion angles of the five metatarsals were calculated by defining the dorsopalmar vector of the metatarsal base and the vector corresponding to the rotational axis of the metatarsal head. The present result demonstrated that the second metatarsals of females were significantly more inverted with increasing age. Flat foot is known to be most common in elderly women. Whether there is a cause–effect relationship between second metatarsal torsion and flattening of the medial longitudinal arch has yet to be answered, but this study suggested that torsion of the second metatarsal might possibly be used as an indicator for the early diagnosis of flat foot and associated foot pathologies. Clin. Anat. 30:1058–1063, 2017. © 2017 Wiley Periodicals, Inc.